2012
DOI: 10.4254/wjh.v4.i4.110
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial translocation and changes in the intestinal microbiome associated with alcoholic liver disease

Abstract: Alcoholic liver disease progresses through several stages of tissue damage, from simple steatosis to alcoholic hepatitis, fibrosis, or cirrhosis. Alcohol also affects the intestine, increases intestinal permeability and changes the bacterial microflora. Liver disease severity correlates with levels of systemic bacterial products in patients, and experimental alcoholic liver disease is dependent on gut derived bacterial products in mice. Supporting evidence for the importance of bacterial translocation comes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 90 publications
3
69
0
1
Order By: Relevance
“…Since this microbe is able to degrade mucin, 21,22 some authors hypothesised that it could promote bacterial translocation (one of the factors involved in alcohol liver injury). 23 Moreover, Yan and colleagues in the same study showed that the population of Lactobacilli was depleted in alcohol-treated mice. 20 This last evidence could explain the beneficial effect of probiotics in the prevention of increased gut permeability, endotoxinemia and liver injury reported in alcoholfed mice.…”
Section: Alcohol-induced Changes On Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…Since this microbe is able to degrade mucin, 21,22 some authors hypothesised that it could promote bacterial translocation (one of the factors involved in alcohol liver injury). 23 Moreover, Yan and colleagues in the same study showed that the population of Lactobacilli was depleted in alcohol-treated mice. 20 This last evidence could explain the beneficial effect of probiotics in the prevention of increased gut permeability, endotoxinemia and liver injury reported in alcoholfed mice.…”
Section: Alcohol-induced Changes On Gut Microbiotamentioning
confidence: 99%
“…Moreover the effects of probiotics are strain-dependent, therefore, further clinical studies are warranted to determine which probiotic strain should be used and which patient population should be treated. 23 Finally, further studies are warranted to assess the safety of administration of probiotics, in particular in patients with gut barrier leakage for the possible higher risk of systemic infection. 69,70 Another group of molecules able to modify gut microflora is represented by prebiotics.…”
Section: Role Of Gut Microbiota In Alcoholic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial translocation from the GI tract to the peripheral circulation has been extensively studied in HIV infection, but is also common in liver disease and other conditions (24)(25)(26)(27). Translocation occurs early in HIV infection due to depletion of gut CD41 lymphocytes and is not completely eradicated by ART, particularly in patients with a suboptimal CD4 cell count or HIV viral level responses (25,28).…”
Section: Bacteria and The Gi Tractmentioning
confidence: 99%
“…These pathological alterations can directly or indirectly promote inflammation and fibrosis in fatty liver [50] . For instance, alcohol and obesity/diabetes lead to quantitative and qualitative changes of the microbiome and an impaired intestinal barrier, and these mechanisms are known to promote hepatic inflammation, fibrosis and cancerogenesis [51,52] . One further example is (visceral) adipose tissue, in which secretion of adipokines is altered by both obesity and alcohol.…”
Section: Extrahepatic Mechanisms Affecting Disease Progression In Aldmentioning
confidence: 99%